2021
DOI: 10.1016/j.omtn.2021.02.021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-29b regulates diabetic aortic remodeling and stiffening

Abstract: Patients with type 2 diabetes (T2D) are threatened by excessive cardiovascular morbidity and mortality. While accelerated arterial stiffening may represent a critical mechanistic factor driving cardiovascular risk in T2D, specific therapies to contain the underlying diabetic arterial remodeling have been elusive. The present translational study investigates the role of microRNA-29b (miR-29b) as a driver and therapeutic target of diabetic aortic remodeling and stiffening. Using a murine model (db/db mice), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…Pretreatment of cardiac fibroblast cells with miR-29b-3p mimics abrogated TGF-β1-induced fibroblast activation, cell proliferation, and reduced the expression of collagen I, collagen III, α-SMA, MMP2, and MMP9 protein [106]. miR-29b can regulate remodeling and stiffening of the aortic valve in db/db diabetic mice [107]. The reduction in the level of miR-29b was attributed to the abundance of expression of its target genes Col1a1 and Mmp2.…”
Section: Discussionmentioning
confidence: 98%
“…Pretreatment of cardiac fibroblast cells with miR-29b-3p mimics abrogated TGF-β1-induced fibroblast activation, cell proliferation, and reduced the expression of collagen I, collagen III, α-SMA, MMP2, and MMP9 protein [106]. miR-29b can regulate remodeling and stiffening of the aortic valve in db/db diabetic mice [107]. The reduction in the level of miR-29b was attributed to the abundance of expression of its target genes Col1a1 and Mmp2.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that miR-29b is remarkably downregulated in db/db mice. 31 A recent study demonstrated that miR-29b upregulation could inhibit cardiac fibrosis in CFs and in a mouse myocardial infarction model. 32 In the present study, the upregulated circRNA_41535 and circRNA_20422 in DCM mice have binding sites with miR-29b-2-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Estos factores inductores también son regulados por miARN. Por lo tanto, es razonable pensar que la regulación a la baja de algunos miARN permita el incremento de estos inductores, favoreciendo el desarrollo de la ND, como se muestra en la tabla 2 25,[35][36][37][38][39][40] . Se ha reportado que en modelos murinos con ND, miR-488 regula la expresión de TGF-β, el cual es un fuerte factor fibrótico que se expresa principalmente en riñón y que se distribuye abundantemente en glomérulos y túbulos renales, participando en el proceso patológico de la fibrosis renal, sugiriendo que miR-488 podría ser una nueva diana terapéutica para ND 41 .…”
Section: Miarn Circulantes Como Biomarcadores En La Predicción De La ...unclassified